(untitled) (Al-Aasar, 2025)
This research critically examines Allama Muhammad Iqbal’s poetry and prose in relation to colonial mentality and the philosophical concept of Khudi (selfhood). The study explores how Iqbal’s literary works articulate a comprehensive critique of colonial psychological, intellectual, and cultural domination, while simultaneously proposing a constructive framework for individual and collective self-realization. Colonial mentality, characterized by internalized inferiority, blind imitation, and intellectual stagnation, is identified as a central obstacle to the spiritual and cultural development of Muslim societies. Iqbal’s poetry, through symbolic imagery and intertextual references to Islamic philosophy and Quranic teachings, cultivates consciousness and encourages the awakening of Khudi, empowering individuals to resist subjugation and rediscover their creative and moral capacities. In prose, Iqbal provides a systematic and analytical approach, engaging with Western philosophical thought, modern science, and educational principles to illustrate the contrasts between colonial intellectual imposition and the emancipatory potential of Islamic thought. His writings emphasize the importance of education, critical reasoning, and ethical development as tools to cultivate Khudi and counteract colonial domination. The study identifies the structural and thematic features of Iqbal’s literary texts, including his use of metaphor, symbolism, and logical argumentation, which collectively establish a coherent and persuasive framework for intellectual and spiritual emancipation. The research demonstrates that the concept of Khudi is not only a philosophical or ethical principle but also a practical guide for personal and societal transformation. It fosters self-reliance, creative initiative, and moral autonomy, offering a sustainable model for resisting colonial and post-colonial influences. By integrating poetry and prose, Iqbal constructs a unified discourse that simultaneously nurtures aesthetic appreciation, ethical consciousness, and critical awareness. This dual approach, combining symbolic literary expression and systematic analytical reasoning, reinforces the transformative potential of Khudi as a mechanism for overcoming internalized subjugation. The study concludes that Iqbal’s literary and philosophical contributions remain highly relevant for contemporary Muslim societies, offering both theoretical insight and practical guidance for intellectual revival and cultural resilience. By engaging with his critique of colonial mentality and the conceptual framework of Khudi, individuals and communities can cultivate agency, reinforce selfhood, and achieve creative and ethical development, thereby contributing to the revival of both personal and collective identity.